The effect of 2 mMol glutamine supplementation on HSP70 and TNF-α release by LPS stimulated blood from healthy children. Issue 6 (December 2015) - Marino, L.V.; Pathan, N.; Meyer, R.; Wright, V.J.; Habibi, P.
Summary: Objective: Glutamine has been shown to promote heat shock protein 70 (HSP70) release both within experimental in vitro models of sepsis (2–10 mM) and in adults post trauma (0.5 g/kg), although the efficacy varies and is dependent on the model used. The effect of glutamine supplementation on HSP70 release in children is less clear. Therefore, the aim of this study was to investigate the effect of 2 mM glutamine added to incubation media on HSP70 and inflammatory mediator release in an in vitro model of paediatric sepsis using whole blood from healthy paediatric volunteers. Methods: An in vitro whole blood endotoxin stimulation model using 1 μg/ml lipopolysaccharide (LPS) over a 24 h time period was used to investigate the effects of 2 mM glutamine on HSP70 and inflammatory mediator release in healthy children. Results: The addition of 2 mM glutamine to the incubation media significantly increased HSP70 release over time (p < 0.05). This was associated with an early pro-inflammatory effect on TNF-α release at 4 h (p < 0.005) which was not seen at 24 h. There was a non significant trend towards higher levels of IL-6 and IL-10 following the addition of 2 mM glutamine, which appears to differ from the response reported in adult and animal models. Conclusion: Glutamine supplementation of incubation media promotes HSP70 and early TNF- α release in an in vitro model using blood samples from healthy children.